Inovasi Teknologi Envair (Ensilase Vacuum Air) dan Levelling Bahan Aditif Lokal Untuk Meningkatkan Kualitas Silase Berbasis Hijauan Ruminansia - Alfan Setya Winurdana; Resti Yuliana Rahmawati; Galih Setya Saputra (Journal of Livestock Science and Production, 2025)
Ensuring continuous forage availability for ruminants remains a major challenge in livestock production, as silage making is often constrained by the risk of preservation failure. This study was conducted to evaluate the effect of vacuum air application (A1 = with vacuum air, A2 = without vacuum air) and different levels of molasses on the quality of corn stover silage. The experiment used a completely randomized factorial design with two factors, namely vacuum air (A1 and A2) and molasses levels (B1 = 2%, B2 = 3%, and B3 = 4% of fresh weight), each repeated five times. Parameters observed included pH, dry matter, organic matter, and crude protein. The results showed that vacuum air (A1) significantly increased dry matter, organic matter, and crude protein content (P0.05) compared to without vacuum air (A2), but had no effect on silage pH. Molasses addition also significantly affected dry matter, organic matter, and crude protein (P0.05), with B2 (3%) producing the highest values compared to B1 (2%) and B3 (4%), while pH remained unaffected. Furthermore, there was a significant interaction between vacuum air and molasses levels on crude protein content (P0.05). Overall, silage pH values ranged from 3.52 to 3.71, indicating stable acidity across treatments. It was concluded that the combination of vacuum air (A1) and molasses at 3% (B2) was the most effective treatment to improve the nutritional quality of corn stover silage, as indicated by higher dry matter, organic matter, and crude protein contents with stable pH values.